Modernity and the regulation of bodies: Elias meets Foucault - Carlos José Martins; Jorge Andrés Jiménez Muñoz (Motriz: Revista de Educacao Fisica, 2019)
ABSTRACT This article seeks to reflect on the possibility of a meeting ground where Michel Foucault and Norbert Elias’ thought comes together around the issue of the regulation of drives and bodily practices within modernity. Such drives - among which we highlight the use of force and violence, as well as the acceptable regulation of their release and applications - have been the object of particular procedures within the modern era, whether seen in relation to individuals or from to the social body.